Manipulation of sarcoplasmic reticulum Ca2+ release in heart failure through mechanical intervention. (17th June 2015) - Ibrahim, Michael; Nader, Anas; Yacoub, Magdi H; Terracciano, Cesare
Abstract : Left ventricular assist devices (LVADs) were developed as a means of temporary circulatory support, but the mechanical unloading they offer also results in significant reverse remodelling. In selected patients, these improvements are sufficient to allow ultimate device explantation without requiring transplantation; this represents a fundamental shift in our understanding of heart failure. Like heart failure itself, LVADs influence multiple biological systems. The transverse tubules are a system of membrane invaginations in ventricular cardiomyocytes which allow rapid propagation of the action potential throughout the cell. Through their dense concentration of L‐type Ca 2+ channels in close proximity to intracellular ryanodine receptors, the t‐tubules enable synchronous Ca 2+ release throughout the cell. The t‐tubules' structure appears to be specifically regulated by mechanical load, such that either the overload of heart failure (or the spontaneously hypertensive rat model) or the profound unloading in a chronically unloaded heart result in impaired t‐tubule structure, with ineffective Ca 2+ release. While there are multiple molecular pathways which underpin t‐tubule regulation, Telethonin (Tcap) appears to be important in regulating the effect of altered loading on the t‐tubule system.